Assessing the Health Risk and Trophic Transfer of Lead and Cadmium in Dairy Farming Systems in the Mantaro Catchment, Central Andes of Peru - Chirinos-Peinado, Doris (2024)
This study investigated lead (Pb) and cadmium (Cd) transfer in three dairy farming areas in the Mantaro river headwaters in the central Peruvian Andes and at varying distances from the mining complex at La Oroya. At each of these sites, the transfer of trace metals from the soil to raw milk was estimated, and a hazard assessment for lead and cadmium was carried out in scenarios of minimum, average, and maximum milk consumption in a Peruvian population aged 2–85. Pb and Cd were quantified by flame atomic absorption spectrometry. Significantly, the concentrations of lead and cadmium were found to exceed the maximum limits recommended by the World Health Organization, with a positive geospatial trend correlated with the distance from mining activity. Both Pb and Cd were found to be transferred through the soil–pasture–milk pathway, with the primary source of Cd being phosphate-based fertilizers used in pasture improvement. Pb was found to be the most significant contributor to the Hazard Index (HI) with those under 19 years of age and over 60 recording an HI of >1, with infants being the most vulnerable group due to their greater milk consumption in relation to their body weight. A marginal increase in contamination was observed in the dry season, indicating the need for studies to be expanded over several annual cycles.